Correlação entre indicadores de desenvolvimento mundial e o número de certificações ISO 9001 e ISO 14001 - Toporowicz, Flávia Zabloski (2018)
The ISO 9001 and ISO 14001 certifications have become the most well-known standard in the world for their diffusion in hundreds of countries, since the need to use technical certifications to unify customer requirements standards. Every year, ISO Survey reports are released to demonstrate the number of valid certifications by country and by sector. From this, questions have arose about what could influence the number of ISO certifications in different countries. In this sense, this work objective was to identify the World Development Indicators that have correlation with the number of ISO 9001 and ISO 14001 certifications. For this, the data was collected from the ISO Survey and World Bank Data databases, using a filter for the categories: economy, education, environment, financial sector, infrastructure, private sector and commerce, and public sector. Due to the large volume of data, the software WEKA was used for dimensionality reduction and data mining, in order to obtain a subset with the same integrity as the original data. Afterwards, the indicators selected were analyzed statistically in the SPSS software in search of significant correlations between indicators and certifications ISO 9001 and ISO 14001, considering a period of ten years (2007 to 2016). The findings show similarities in the correlations with the existing studies, between the number of certifications and the indicators Merchandise Exports (US$), Gross Domestic Product – GDP (US$), Labor Force (total), Gross National Income – GNI (US$) and Population (total). Also, the finding show correlations that were not explored by the existing literature, as Scientific and Technical publications, Passenger transportation, Greenhouse Emissions, Methane Emissions, and Nitrous Oxide Emissions. This study contributes to the understanding of managers, researchers, and certification agents about the identification of indicators that can have influence on the adoption of the international certifications ISO 9001 and ISO 14001 in countries. Also, it shows that the development, the economy and the infrastructure, as well as the scientific development of the countries are related to the certifications adoption.